Back to the futures: An assessment of commodity market efficiency and forecast error drivers - Bernardina Algieri; Matthias Kalkuhl (University of Bonn, Center for Development Research (ZEF), 2014)
The role of futures markets in stabilizing spot prices has been extensively discussed. Nevertheless, the ability of these markets to achieve the stabilizing function significantly depends on whether they are "efficient" in the sense that futures prices "fully reflect" the available information. The purpose of this study is first to gauge the extent to which futures markets for a set of traded commodities can be considered efficient in predicting spot prices. We then go beyond traditional analyses of efficiency and assess the relative forecasting performance of futures markets; i.e., the difference between the realization and prediction of future spot prices, and what factors affect these forecast errors. The results of the analysis show that maize, soybeans, and wheat markets are not informationally efficient, so that investors can make outsize profits. We find that short-term speculation, measured by the scalping index, increases the noises in the information formation process, thus increasing forecast errors. Conversely, long-term speculation, proxied by the Working-T index and the speculative pressure index, reduces forecast errors although their quantitative effect is negligible. Other relevant factors that drive forecast errors up are a high level of realized price volatility, the lack of liquidity in the market, and a longer contract maturity horizon.
Keywords: G14; C58; Q14; 330; futures markets; efficiency; forecast errors; GARCH